APLIKASI PRINSIP INKLUSI EKSKLUSI DALAM METODE KOMBINASI SENSUS PENDUDUK 2020 - Notiragayu Notiragayu; Amanto Amanto; Dorrah Aziz (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2019)
The 2020 population census (SP 2020) uses a new method called the combination method by utilizing basic population registration data available at the Directorate General of Civil Registration, the community register independently (CAWI) and door to door data collection by officers (PAPI and CAPI). Data on the number, composition, distribution, and characteristics of the population with this new method is prone to overlapping, one data is counted several times which results in the calculation of bias from the actual amount. This paper shows how the principle of exclusion inclusion can be applied to overcome data that is counted several times. Keywords : combined method, overlapping, The Principle of Inclusion-Exclusion